An Analysis Of Illocutionary Speech Acts In Prabowo Subianto's Speech At The Unite Nations General Assembly On September 23, 2025 - Agustina rotua Purba; sahlan tampubolon; Harpen H.P Silitonga (Visi Sosial Humaniora, 2026)
This research investigates the use of illocutionary speech acts in Prabowo Subianto’s speech at the United Nations, aiming to identify the types of illocutionary acts and their functions in political discourse. The study employs a qualitative descriptive approach grounded in pragmatic theory, focusing on the classification of speech acts based on Searle’s framework: representative, directive, commissive, expressive, and declarative. The data were collected from the speech transcript and analyzed through data condensation, data display, and conclusion drawing. The findings reveal that representative acts dominate the speech 50%, indicating the speaker’s emphasis on conveying facts, beliefs, and social or humanitarian realities. Directive acts account for approximately 23,08%, reflecting efforts to persuade and motivate the audience to take collective action. Commissive acts represent 19,23% of the utterances, demonstrating commitments and promises, particularly concerning Indonesia’s contributions to global peacekeeping and international development. Expressive acts make up around 7,69%, showing emotional engagement and moral concern, while declarative acts are absent, suggesting a focus on persuasion and ethical appeal rather than formal institutional action. The study concludes that Prabowo Subianto’s speech effectively combines informative, persuasive, and ethical strategies, with a strong emphasis on representative and directive illocutionary acts to inform, inspire, and mobilize the international audience. This research contributes to the understanding of pragmatic functions in political discourse and provides insights for speakers, educators, and researchers in applying illocutionary theory to real-world communication. In conclusion, the dominance of representative acts, supported by directive and commissive acts, demonstrates that Prabowo Subianto’s speech functions mainly as a diplomatic and persuasive political discourse aimed at informing, influencing, and fostering international cooperation. This study contributes to the field of pragmatics by providing insight into the use of illocutionary speech acts in political speeches delivered at international forums.